Free base phthalocyanine coating as a superior corrosion inhibitor for copper surfaces: a combined experimental and theoretical study - Samal, Pragnya Paramita; Dekshinamoorthy, Amuthan; Arunachalam, Shivakami; Vijayaraghavan, Saranyan; Krishnamurty, Sailaja (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2022)
In the quest of novel, eco-benign copper corrosion inhibitors, free base and a set of six metal Phthalocyanine (Pc) coatings (where metal is Zn, Cu, Fe, Co, Ni, Mn) are systematically evaluated for their corrosion inhibition efficiency. The study demonstrates that the free base Phthalocyanine coatings are superior corrosion inhibitors for Cu surface in HCl with a corrosion inhibition efficiency of 88% as compared to its metal counterparts. A detailed and indepth study involving concerted electrochemical polarisation, impedance measurements at various concentrations of HCl assert the superior corrosion inhibition efficiency of free base Pc coatings as compared to its metal counterparts. Underlying factors/interface chemistry contributing to it is brought out using first principle based studies. First principles based computational studies establish that superior corrosion inhibition ability of free base phthalocyanine molecule is attributed to its innate binding ability with copper surface and its better inter-molecular packing. Thus, the theoretical adsorption trends of various studied phthalocyanine molecules while clearly following the experimental corrosion inhibition efficiency trends undermine the importance of contribution of chelating factors for the formation of a stable and efficient corrosion inhibition coating on a surface and that the adhesion/adsorption strength of a molecule correlates directly to its corrosion inhibition efficiency. The experimental observations are further substantiated through FE-SEM, EDAX and XPS studies. The corrosion inhibition efficiency of free base phthalocyanine is followed by its zinc based counterpart at 85%.
Keywords: Copper surface; Corrosion inhibitors; DFT studies; Impedance; Phthalocyanine coatings

Expounding lemonal terpenoids as corrosion inhibitors for copper using DFT based calculations - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Applied Surface Science, 2023)
The most important bottleneck in identifying an innovative and yet viable corrosion inhibitor for copper surfaces is discerning the chemical interactions at the interface of adsorbate and adsorbent. The present work, primarily, discerns the interface chemistry of green corrosion inhibitors, viz., lemonal terpenoids, with the copper surfaces for the first time. The interface chemistry is evaluated for distinct facets of copper, modelled by periodic surfaces to finite sized aggregates, with two stereoisomers viz., citral and neral through density functional calculations. The adsorption/ interaction properties between the surface and the corrosion inhibiting molecule are analysed through the electronic properties such as density of states, charge density difference plots and Bader charges where in distinct bonding mechanisms are identified as a function of varying facets. Apart from the adsorption properties, molecular packing properties are of paramount importance towards the design of an efficient corrosion inhibitor for a surface. Hence, we also analyse the intermolecular stacking energies between the inhibitors when packed among themselves in vacuum and when adhered on to metal surfaces. The studies bring forth an understanding that lemon terpenoids are highly potential corrosion inhibitors for copper surfaces, particularly, for Cu (110) surfaces both in neutral and protonated form.
Keywords: Copper surface; Density Functional Theory (DFT); Green corrosion inhibitors; Interface chemistry; Lemonal terpenoids; Molecular stacking